Activation of serum 5′ nucleotidase by magnesium ions and its diagnostic applications. Issue 2 (March 1969) - Belfield, A.; Goldberg, D. M.
Abstract : Magnesium ions increase the hydrolysis of adenosine 5′ monophosphate (5′ AMP) by human serum at p H 7·9 but not at p H 9·3. The additional hydrolysis at p H 7·9 is predominantly due to increased activity of the specific phosphatase 5′ nucleotidase (5Nase). This increase is proportional to enzyme concentration and has been employed as a measure of 5Nase activity in a sensitive micro-estimation. The normal range for serum 5Nase activity by this technique was 0 to 20 mIU/ml. In a series of over 200 patients, raised values were found frequently in hepatobiliary disease and infrequently in bone disease. Assay of 5Nase activity gave a more reliable indication of the source of raised serum alkaline phosphatase than isoenzyme electrophoresis in agar gel. The correlation between activities of the two enzymes was low in bone disease generally, and fairly good in hepatobiliary disease. The closest correlation was found in patients with parenchymal liver disease.